Norbornene monomer, norbornene polymer, preparation method of norbornene polymer, block polymer and application of block polymer
By designing the method of connecting ester groups to fluorene in norbornene monomers, combined with the ring-opening metathesis polymerization of Grubbs I catalyst, polymers with high glass transition temperature and controllable molecular weight were prepared, which solved the problem of low glass transition temperature of existing norbornene polymers, and achieved precise control of morphology and large-scale production during the PISA process.
Patent Information
- Application Number
- CN202510056949.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-25
AI Technical Summary
The glass transition temperature of existing norbornene polymers is low, making it difficult to meet the needs of a variety of application scenarios. At the same time, there are challenges in morphology control and large-scale production during PISA.
By designing the ester group to connect to fluorene at the 2 and 3 positions of norbornene, a macrocyclic structure norbornene monomer is formed, and ring-opening metathesis polymer is performed using Grubbs I catalyst to prepare polymers with high glass transition temperature and molecular weight controllable. This polymer is used as a hydrophobic section for self-assembly of amphiphilic polymers, achieving a non-repeatable worm morphology.
The glass transition temperature of the polymer is significantly improved to reach 245-265℃, and the molecular weight distribution is controlled, the application range of polymers is expanded, and the precise control of morphology and large-scale production are achieved during the PISA process.
Smart Images

Figure CN119874664A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of polymer synthesis, and specifically relates to a norbornene monomer and a polymer prepared therefrom, and a preparation method and application thereof Background Art
[0002] Ring-opening metathesis polymerization (ROMP) is an important polymerization method that is widely used in the preparation of high-performance polymers. By selecting appropriate monomers and catalysts, polymers with specific properties and functions can be designed. This method is particularly suitable for the preparation of cyclic olefin polymer materials. In the study of cyclic olefins, norbornene and its derivatives have attracted widespread attention due to their high reactivity. Norbornene polymers prepared by ROMP usually show high T g , which enables it to maintain good physical properties under high temperature conditions; and the polymer has excellent light transmittance, making it suitable for use in optical materials, coatings and packaging.
[0003] In order to further improve the performance of norbornene polymers, we tried to introduce substituents into their structures. Fluorene is an important aromatic compound with unique physical and chemical properties and is widely used in organic electronics, optoelectronic materials, polymer science and other fields. The introduction of such substituents can not only improve the structural properties of the polymer, but also expand its application areas. Specifically, amphiphilic block polymers containing fluorene structures exhibit excellent crystallization-driven self-assembly properties. Prior art US7763691B2 discloses a norbornene monomer with a fluorene group and a polymer prepared therefrom, but the glass transition temperature (Tg) of this polymer is relatively low, only about 80°C, which is difficult to meet the needs of many application scenarios. Therefore, developing a new monomer structure to prepare a polymer with good crystallization performance and high Tg, and an insoluble block with high Tg and π-π stacking effect helps to achieve precise control of the morphology and large-scale production during the PISA process, and expanding the morphological diagram of the worm structure is a challenge in this field. Summary of the invention
[0004] In order to solve the above-mentioned technical problems, the present invention provides a norbornene monomer, and efficiently synthesizes a polymer with controllable molecular weight, narrow molecular weight distribution and high Tg through ring-opening metathesis polymerization using a Grubbs I catalyst, and uses the polymer as a hydrophobic segment to prepare an amphiphilic polymer for polymerization-induced self-assembly to obtain a worm-like morphology that is not easy to repeat.
[0005] To achieve the above-mentioned purpose of the invention, on the one hand, the present invention provides a norbornene monomer, the structural formula of which is shown below: Compared with the norbornene fluorene monomer in the US patent in the background technology, the present invention designs ester groups at the 2-position and 3-position of norbornene to connect with fluorene, thereby forming a macrocyclic structure between norbornene and fluorene. Through such molecular design, it is expected to improve the molecular rigidity, thereby further improving the glass transition temperature of the polymer formed by polymerization.
[0006] Another aspect of the present invention is to provide a polymer obtained by polymerization of the above-mentioned norbornene monomer, the structure of which is shown below:
[0007]
[0008] Wherein, n is a positive integer such that the number average molecular weight of the polymer is between 5000 and 30000, and the molecular weight distribution of the polymer is 1.10-1.20.
[0009] In a preferred embodiment, the glass transition temperature of the polymer is 245-265°C. The polymer with a molecular weight between 5000 and 30000 has a glass transition temperature within the above range according to the specific degree of polymerization, which can be specifically 251°C, 253°C, 254°C, 257°C and 258°C, etc., and those skilled in the art can expect that the prepared polymer can have a glass transition temperature within the range of 245-265°C by specific adjustment according to the molecular weight. Compared with the polymer shown in US7763691B2, by designing an ester group at the 2nd and 3rd positions of the norbornene monomer to connect with fluorene, a macrocyclic structure is formed between norbornene and fluorene. Through such molecular design, the molecular rigidity is improved, so that the glass transition temperature of the polymer prepared therefrom is greatly improved, and the polymer with a high glass transition temperature can greatly expand its own application range.
[0010] Another aspect of the present invention is to provide a method for preparing the above polymer, comprising the following steps:
[0011] S1, after placing the Grubbs I catalyst in a reactor, filling the reactor with an inert gas to exhaust air, injecting an anhydrous organic solvent into the reactor under an inert gas environment, and after the anhydrous organic solvent fully dissolves the catalyst, adding the norbornene monomer dissolved in the organic solvent dropwise therein;
[0012] S2, react at room temperature for 7-10 hours;
[0013] S3. After the reaction is completed, post-processing is performed on the polymer generated by the reaction to obtain the polynorbornene fluorene polymer.
[0014] In a preferred embodiment, the inert gas is selected from one or more of nitrogen, helium and argon.
[0015] In a preferred embodiment, the molar ratio of the Grubbs I catalyst to the norbornene fluorene monomer is 1:(20-100).
[0016] In a preferred embodiment, the anhydrous organic solvent is anhydrous dichloromethane.
[0017] In a preferred embodiment, the post-treatment operation includes adding a methanol solution to quench the reaction so that the polymer obtained by the reaction is precipitated, and then filtered, washed with a methanol solution, and then centrifuged and dried to obtain the polymer.
[0018] Another aspect of the present invention is to provide a block polymer prepared from the above polymer, the structural formula of which is shown below:
[0019]
[0020] Wherein, m and n are positive integers such that the number average molecular weight of the block copolymer pair is between 10,000 and 40,000, and the molecular weight distribution is 1.25-1.35.
[0021] Another aspect of the present invention is to provide an application of the block copolymer, wherein the block copolymer is dissolved in a mixed solvent of tetrahydrofuran and water to obtain a block copolymer worm thread; wherein the volume ratio of tetrahydrofuran to water is 1:1.
[0022] The present invention provides a norbornene polymer, which can be polymerized by ring-opening metathesis using a Grubbs I catalyst, and the formed polymer has the characteristics of high glass transition temperature, controllable molecular weight, narrow molecular weight distribution, etc. The polymer with high glass transition temperature is used as a hydrophobic segment to synthesize an amphiphilic copolymer to induce polymerization self-assembly to obtain a worm-like morphology that is not easy to form, thereby expanding the experimental window of the worm structure in ROPISA. The worm-like polymer assembly may have unique electrical, optical, biocompatibility or self-assembly properties, etc. The realization and regulation of these properties all depend on the stable preparation and morphological regulation of the worm structure. This makes the norbornene polymer with high glass transition temperature have broad application prospects in the fields of materials science, biomedicine, nanotechnology, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the hydrogen spectrum of monomer 1 obtained in Example 1.
[0024] Figure 2 This is the carbon spectrum of monomer 1 obtained in Example 1.
[0025] Figure 3 is the HRMS chart of monomer 1 obtained in Example 1.
[0026] Figure 4 This is a diagram of the single crystal structure of monomer 1 obtained in Example 1.
[0027] Figure 5 The polymer poly-1 obtained in Example 2 n The hydrogen spectrum of .
[0028] Figure 6 is the gel permeation chromatogram of each polymer involved in Examples 2-6.
[0029] Figure 7 is the infrared spectrum of the polymer obtained in Example 2.
[0030] Figure 8 is the DSC chart of the polymer obtained in Example 2.
[0031] Fig. 9 It is the gel permeation chromatogram of each block polymer involved in Examples 7-11.
[0032] Fig.10 It is the hydrogen spectrum of the amphiphilic block copolymer.
[0033] Fig.11 is a SEM image of the worm morphology obtained from the amphiphilic block copolymer. DETAILED DESCRIPTION
[0034] The present application will be further described below in the form of specific embodiments. A person skilled in the art will be able to implement the present application based on these descriptions.
[0035] Example 1
[0036] The synthesis of norbornene monomer, the specific synthesis process is: 10.98mmol of 5-norbornene-2,3-dicarboxylic acid and 26.6mmol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDCI) are dissolved in a round-bottom flask equipped with a stirring bar, and the round-bottom flask is filled with 50mL of dichloromethane. Stir the reaction mixture until the solid is completely dissolved. At the same time, 11.05mmol of 9H-fluorene-9,9-diethanol, 19.6mmol of 4-dimethylaminopyridine (DMAP) and 50mL of dichloromethane are added to the culture bottle. While stirring, the solution in the culture bottle is added dropwise to the culture bottle containing 5-norbornene-2,3-dicarboxylic acid / EDCI solution through an addition funnel. The reaction mixture is stirred at room temperature until the starting material is completely consumed by TLC, and the reaction time is 12 hours. The reaction mixture was then transferred to a separatory funnel, washed twice with 40 mL of water, then once with 40 mL of saturated brine, the organic phase was dried over Na2SO4, and concentrated by rotary evaporation to obtain a crude product. The crude product was purified by automated flash chromatography on silica using a petroleum ether / ethyl acetate mixture (10:1) as the mobile phase to obtain 2.8 g of a white solid. The synthetic route is as follows:
[0037]
[0038] The hydrogen spectrum, carbon spectrum and MALDI-TOF MS spectrum of the new substance monomer are shown in Figure 1-3 It can be seen that all hydrogen and carbon elements appear in corresponding positions, indicating that new substances with corresponding structures have been prepared. Figure 3 It can be seen that the difference between each peak is about 372, which is the same as the expected molecular weight.
[0039] Example 2
[0040] The polymer was prepared from the monomers synthesized in Example 1. The specific polymerization process was as follows: a stirring rod and 7×10 Grubbs I catalyst were added to a dry round-bottom flask. -3 mmol. The culture bottle was then sealed with a rubber diaphragm and purged with N2 for 10 minutes. Then, 1 mL of dry, air-free dichloromethane was added through a syringe, and the catalyst was dissolved by stirring. A dichloromethane solution containing 0.134 mmol of the norbornene fluorene monomer prepared in Example 1 was placed in a dry N2-purged vial equipped with a rubber diaphragm, wherein the dichloromethane was 0.5 mL. The above-mentioned norbornene fluorene monomer solution was then added to a round-bottom flask containing the GrubbsI catalyst solution through a syringe, and the solution was stirred at room temperature for 7 hours. After the reaction was completed, the reaction solution was added dropwise to an excess of methanol, and the resulting polymer precipitated. The polymer was collected by vacuum filtration and then dried under vacuum to obtain 48 mg of the desired product. In this embodiment, the structure of the polymer is
[0041] See attached Figure 4 As shown in the hydrogen spectrum of the obtained polymer, all hydrogen elements appear in corresponding positions, indicating that a polymer with a corresponding structure is prepared. Figure 5 , and its number average molecular weight is 7.6×10 3 Da, molecular weight distribution is 1.13, degree of polymerization n is 20, recorded as poly-1 20 . See attached Figure 5 The characteristic peaks in the infrared spectrum indicate that a polymer with the corresponding structure has been prepared. -1 The characteristic peaks appear near the C—H bond vibration range; at 1757 cm -1 There are characteristic peaks near the C=O bond vibration range; at 1450cm -1 The characteristic peaks appear near the benzene ring vibration range. Figure 8 The glass transition temperature shown by the DSC curve is 251°C.
[0042] Example 3
[0043] The experimental steps are as in Example 2, except that 4.75×10 -3 mmol of Grubbs I catalyst, the mass of the final prepared polymer was 47.2 mg.
[0044] See attached Figure 6 As shown in the figure, the polymer described in this embodiment is poly-1 30 The number average molecular weight of the polymer was 12×10 3 Da, molecular weight distribution is 1.14, and degree of polymerization is 30. The prepared polymer is subjected to DSC test, and the test shows that its glass transition temperature is 253°C.
[0045] Example 4
[0046] The experimental steps are as in Example 2, except that 2.813×10 -3 mmol of Grubbs I catalyst, the mass of the final prepared polymer was 42 mg.
[0047] See attached Figure 6 As shown in the figure, the polymer described in this embodiment is poly-1 50 The number average molecular weight of the polymer was 18.5×10 3 Da, molecular weight distribution is 1.15, and degree of polymerization is 50. The prepared polymer is subjected to DSC test, and the test shows that its glass transition temperature is 254°C.
[0048] Example 5
[0049] The experimental steps are as in Example 2, except that 2.338×10 -3 mmol of Grubbs I catalyst, the mass of the final prepared polymer was 35 mg.
[0050] See attached Figure 6 As shown in the figure, the polymer described in this embodiment is poly-1 60 The number average molecular weight of the polymer was 22.6×10 3 Da, molecular weight distribution is 1.15, and degree of polymerization is 60. The prepared polymer is subjected to DSC test, and the test shows that its glass transition temperature is 257°C.
[0051] Example 6
[0052] The experimental steps are as in Example 2, except that 2.013×10-3 mmol of Grubbs I catalyst, the mass of the final prepared polymer was 33 mg.
[0053] See attached Figure 6 As shown in the figure, the polymer described in this embodiment is poly-1 70 The number average molecular weight of the polymer was 25.2×10 3 Da, molecular weight distribution is 1.16, and degree of polymerization is 70. The prepared polymer is subjected to DSC test, and the test shows that its glass transition temperature is 258°C.
[0054] Example 7
[0055] The synthetic route of the polynorbornene fluorene polynorbornene glycol block copolymer of the present invention is shown in the attached figure, and the specific preparation process is as follows: First, three solutions are prepared under deoxygenation: (a) 0.152mmol norbornene fluorene is dissolved in 1mL H2O, (b) 0.152mmol norbornene glycol is dissolved in 0.8mL THF, and (c) 0.005mmol Grubbs I catalyst is dissolved in 0.2mL THF. Solution (c) is quickly injected into (b), stirred at room temperature, and after 4 hours, the polynorbornene glycol macroinitiator is synthesized. See the attached Fig. 9 As shown in the figure, the polynorbornene glycol polymer described in this embodiment is poly-2 30 The number average molecular weight of the polymer was 10.5×10 3 , the molecular weight distribution is 1.22.
[0056] In a nitrogen atmosphere, the polynorbornene glycol macroinitiator synthesized above was quickly injected into (a) and stirred at room temperature to trigger ROMPISA in a THF / H2O (v / v=1 / 1) mixture. After 8 hours of reaction, n-hexane was added to terminate the reaction. The obtained product was washed with n-hexane for 4-5 times and vacuum dried until the mass remained unchanged to obtain a polynorbornene fluorene polynorbornene glycol block copolymer with a mass of 86 mg. See attached Fig. 9 As shown in the figure, the block copolymer described in this embodiment is poly(2 30 -b-1 30 ), and the number average molecular weight of the block copolymer was 21.1×10 3 , molecular weight distribution is 1.33. In addition, see Appendix Fig.10 This is the hydrogen spectrum of the prepared copolymer, which clearly shows the distribution of hydrogen elements in multiple locations in the copolymer structure, indicating that a copolymer with the following structural formula was prepared.
[0057]
[0058] Embodiment 8,
[0059] The experimental steps were the same as those in Example 7, except that 0.0536 mmol of norbornene fluorene monomer was added, and the mass of the polynorbornene fluorene-polynorbornene ethylene glycol block copolymer finally prepared was 51.2 mg.
[0060] See attached Figure 1 As shown in the figure, the block copolymer described in this embodiment is poly(2 30 -b-1 10 ), and the number average molecular weight of the block copolymer was 15.5×10 3 , the molecular weight distribution is 1.27.
[0061] Embodiment 9,
[0062] The experimental steps are similar to those of Example 7, except that 0.1046 mmol of norbornene fluorene monomer is added, and the mass of the polynorbornene fluorene-polynorbornene glycol block copolymer finally prepared is 75.3 mg.
[0063] See attached Figure 1 As shown in the figure, the block copolymer described in this embodiment is poly(2 30 -b-1 20 ), and the number average molecular weight of the block copolymer was 17.8×10 3 , molecular weight distribution is 1.30.
[0064] Embodiment 10,
[0065] The experimental steps were the same as those in Example 7, except that 0.2305 mmol of norbornene fluorene monomer was added, and the mass of the polynorbornene fluorene-polynorbornene ethylene glycol block copolymer finally prepared was 119.6 mg.
[0066] See attached Figure 1 As shown in the figure, the block copolymer described in this embodiment is poly(2 30 -b-1 50 ), and gel permeation chromatography measurement showed that the number average molecular weight of the block copolymer was 27.5×103 and the molecular weight distribution was 1.27.
[0067] Embodiment 11,
[0068] The experimental steps were the same as those in Example 7, except that 0.3834 mmol of norbornene fluorene monomer was added, and the mass of the polynorbornene fluorene-polynorbornene ethylene glycol block copolymer finally prepared was 170.5 mg.
[0069] See attached Figure 1 As shown in the figure, the block copolymer described in this embodiment is poly(2 30 -b-1 70 ), and the number average molecular weight of the block copolymer was 39.0×10 3 , the molecular weight distribution is 1.31.
[0070] Fig. 9 The gel chromatograms of the polyfluorene polymer and the polynorbornene fluorene-polynorbornene ethylene glycol block copolymers prepared in Examples 7-11 are shown in combination.
[0071] Example 12
[0072] Take the polynorbornene fluorene polynorbornene glycol block copolymer poly(2 30 -b-1 30 ) was diluted to 0.05 mg / mL in a THF / H2O (v / v=1 / 1) mixed solution and then detected by SEM. Fig.11 It is known that Fig.11 The results show that the copolymer solvent polymerization induced self-assembly can obtain the copolymer worm structure, indicating that norbornene fluorene as a hydrophobic block is conducive to obtaining the worm structure in the polymerization induced self-assembly.
[0073] The present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented.
Claims
1. A norbornene monomer, characterized in that: Its structural formula is as follows:
2. A polymer prepared from the norbornene monomer according to claim 1, characterized in that: Its structure is as follows: Wherein, n is a positive integer such that the number average molecular weight of the polymer is between 5000 and 30000, and the molecular weight distribution of the polymer is 1.10-1.
20.
3. The polymer according to claim 2, characterized in that The glass transition temperature of the polymer is 245-265°C.
4. The method for preparing a polymer as claimed in claims 2-3, characterized in that: The following steps are involved: S1, after placing the Grubbs I catalyst in a reactor, filling the reactor with an inert gas to exhaust air, injecting an anhydrous organic solvent into the reactor under an inert gas environment, and after the anhydrous organic solvent fully dissolves the catalyst, adding the norbornene monomer dissolved in the organic solvent dropwise therein; S2, react at room temperature for 7-10 hours; S3. After the reaction is completed, post-processing is performed on the polymer generated by the reaction to obtain the polynorbornene fluorene polymer.
5. The method for preparing a polymer according to claim 4, characterized in that: The inert gas is selected from one or more of nitrogen, helium and argon.
6. The method for preparing a polymer according to claim 4, characterized in that: The molar ratio of the Grubbs I catalyst to the norbornene fluorene monomer is 1:(20-100).
7. The method for preparing a polymer according to claim 4, characterized in that: The anhydrous organic solvent is anhydrous dichloromethane.
8. The method for preparing a polymer according to claim 4, characterized in that: The post-treatment operation includes adding a methanol solution to quench the reaction so that the polymer obtained by the reaction is precipitated, filtering, washing with a methanol solution, and then centrifuging and drying to obtain the polymer.
9. A block polymer prepared from the polymer according to claims 2-3, characterized in that: Its structural formula is as follows: Wherein, m and n are positive integers such that the number average molecular weight of the block copolymer pair is between 10,000 and 40,000, and the molecular weight distribution is 1.25-1.
35.
10. Use of the block polymer according to claim 9, characterized in that The block copolymer is dissolved in a mixed solvent of tetrahydrofuran and water to obtain a block copolymer worm thread; wherein the volume ratio of tetrahydrofuran to water is 1:1.
Citation Information
Patent Citations
Norbornene monomers with fluorene group and polymer material thereof
US7763691B2